Systematic Literature Review: Physical Work Environment Factors Associated with Work Fatigue in Hospital Nurses - Adventina, Twinda; Widanarko, Baiduri (National Journal of Occupational Health and Safety, 2021)
Fatigue in hospital nurses can endanger the safety of both the nurse and the patient. One of the factors that can cause fatigue in hospital nurses is the physical environmental, such as lighting, noise, and work climate. The purpose of this study is to analyze the physical work environment factors (lighting, noise, and work climate) associated with work fatigue in hospital nurses. This is a systematic literature review on studies that discuss physical work environment factors related to work fatigue in hospital nurses published in international journals and local journals that can be accessed through the UI Library, especially those that are Full Open Access. Fourteen articles that discussed the relationship between physical environmental factors and work fatigue in hospital nurses were identified, consisting of 11 articles on the effect of lighting on work fatigue in hospital nurses. 6 articles discussed how noise influenced work fatigue in hospital nurses, and 3 articles discussed the effect of hot work climate on work fatigue in hospital nurses. Based on the review, lighting, noise, and work climate significantly link to work fatigue in hospital nurses.